2020
DOI: 10.1186/s12974-019-1695-x
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of BDNF/TrkB signaling mediated by NMDAR/Ca2+/calpain might contribute to postoperative cognitive dysfunction in aging mice

Abstract: Background: Postoperative cognitive decline (POCD) is a recognized clinical phenomenon characterized by cognitive impairments in patients following anesthesia and surgery, yet its underlying mechanism remains unclear. Brain-derived neurotrophic factor (BDNF) plays an important role in neuronal plasticity, learning, and memory via activation of TrkB-full length (TrkB-FL) receptors. It has been reported that an abnormal truncation of TrkB mediated by calpain results in dysregulation of BDNF/TrkB signaling and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(129 citation statements)
references
References 62 publications
(84 reference statements)
10
119
0
Order By: Relevance
“…Exploratory laparotomy was performed under aseptic conditions with isoflurane anesthesia, as described in previous studies (Qiu et al, 2020 ; Wen et al, 2020 ). This model has been used in studies investigating both postoperative delirium (Peng et al, 2016 ; Lu et al, 2020 ) and postoperative cognitive dysfunction (Kawano et al, 2015 ; Qiu et al, 2020 ), and is referred to as a model for PND in this study, according to the nomenclature recently adopted in major anesthesiology journals. Briefly, mice were anesthetized with 1.8% isoflurane and oxygen at 2 L/min in an induction chamber for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exploratory laparotomy was performed under aseptic conditions with isoflurane anesthesia, as described in previous studies (Qiu et al, 2020 ; Wen et al, 2020 ). This model has been used in studies investigating both postoperative delirium (Peng et al, 2016 ; Lu et al, 2020 ) and postoperative cognitive dysfunction (Kawano et al, 2015 ; Qiu et al, 2020 ), and is referred to as a model for PND in this study, according to the nomenclature recently adopted in major anesthesiology journals. Briefly, mice were anesthetized with 1.8% isoflurane and oxygen at 2 L/min in an induction chamber for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that cognitive deficits induced by surgery in aged mice can be observed on postoperative day 7 (Fu et al, 2020;Qiu et al, 2020). We used open field tests to FIGURE 2 | Effects of elamipretide on the canonical nod-like receptor pyrin domain-containing 3 (NLRP3) inflammasome-caspase-1 pathway in the hippocampus in aged mice after surgery.…”
Section: Elamipretide Attenuates Surgery-induced Cognitive Deficits Imentioning
confidence: 99%
See 1 more Smart Citation
“…The Y-maze was used to evaluate spatial working memory [16], which was performed in a black Plexiglas Y-Maze with three arms (30 cm long × 14 cm wide ×15 cm high) at 120• angles, designated A, B, and C. Each mouse was placed in the center of Y-Maze facing arm A and allowed to explore all three arms of the maze freely for 8 min. The sequence and total number of arms entered were recorded.…”
Section: Y-mazementioning
confidence: 99%
“…However, the mechanisms underlying are still unclear. There are many causes that may contribute to the occurrence of PND, which would nally induce the changes in synaptic plasticity and the consequent observable dysfunction in learning and memory [1].…”
Section: Introductionmentioning
confidence: 99%